Comparative well-to-wheel life cycle assessment of OME3–5 synfuel production via the power-to-liquid pathway. Issue 11 (23rd September 2019) - Hank, Christoph; Lazar, Lukas; Mantei, Franz; Ouda, Mohamed; White, Robin J.; Smolinka, Tom; Schaadt, Achim; Hebling, Christopher; Henning, Hans-Martin
Abstract : In this study, a holistic well-to-wheel (WtW) life cycle assessment of the production and utilization of short oligomers of OME3–5 as produced via a Power-to-Liquid (PtL) pathway has been conducted. Abstract : Oxymethylene Dimethyl Ethers (OMEs) are promising diesel fuel alternatives and interesting solvents for various industrial applications. In this report, a well-to-wheel life cycle assessment of short OME oligomers as produced via a Power-to-Liquid (PtL) pathway has been conducted. Variations in electricity and carbon dioxide supply as well as the hardware demand for the PtL plant components ( e.g. PEM water electrolysis, carbon capturing, and 36 kta OME plant capacity) have been considered. Conventional diesel fuel is used as the comparative benchmark. In scenarios with a high share of renewable electricity well-to-wheel greenhouse gas emission for OME3–5 fuel is advantageous compared to fossil diesel. For the best case, well-to-wheel greenhouse gas emissions can be reduced by 86%, corresponding to 29 g(CO2eq ) km −1 (OME3–5 -fuel) compared to 209 g(CO2eq ) km −1 (diesel fuel). However, these results are highly sensitive to the applied method with regard to system multifunctionality. A sensitivity analysis indicates that input electricity at ∼50 g(CO2eq ) kWhel −1 enables well-to-wheel greenhouse gas emissions of <100 g(CO2eq ) km −1 . For other environmental impact categories, acidification, eutrophication, respiratory effects, photochemical ozone creation and resource depletion exceed significantly the fossil fuel reference. A high share of these impacts can be assigned to electricity production, either through direct electricity consumption in the PtL system or during upstream production of hardware components. The presented results and discussion demonstrate the necessity for global defossilisation including material efficient manufacturing of renewable energy plants which remains mandatory for synfuel production addressing a wide range of environmental impact categories. Furthermore, PtL production concerning well-to-wheel greenhouse gas emissions could be beneficial even in Germany if dedicated renewable energy capacities are considered. However, operation of large-scale PtL plants will predominantly be conducted in countries with high renewable energy potential, resulting in low levelized cost of electricity and high full load hours.